2018
DOI: 10.1002/hpja.4
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of the role of playgroups in building community capacity

Abstract: Community playgroups play a key role in building the capacity of communities and provide a vehicle for the development of new volunteers. SO WHAT?: Local governments, schools and other community organisations that rely on volunteer committees would benefit from providing support to community playgroups to foster future community leaders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 17 publications
(25 reference statements)
1
16
0
Order By: Relevance
“…Of these five studies, one was undertaken in an Australian Indigenous community (Fleer & Hammer, 2014). From the demographic details about participants that were provided, two studies were undertaken with participants predominantly from middle to upper socioeconomic backgrounds (Keam et al, 2018; Mulcahy, Parry, & Glover, 2010), a further two were undertaken in metropolitan areas (Gibson et al, 2015; Harman et al, 2014) and one in rural Victoria (Fleer & Hammer, 2014). Four out of the five studies reported the use of a theoretical orientation informing the research, including social capital (Gibson et al, 2015), interpretative phenomenological (Harman et al, 2014), cultural-historical (Fleer & Hammer, 2014) and critical social capital (Mulcahy et al, 2010) theories.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these five studies, one was undertaken in an Australian Indigenous community (Fleer & Hammer, 2014). From the demographic details about participants that were provided, two studies were undertaken with participants predominantly from middle to upper socioeconomic backgrounds (Keam et al, 2018; Mulcahy, Parry, & Glover, 2010), a further two were undertaken in metropolitan areas (Gibson et al, 2015; Harman et al, 2014) and one in rural Victoria (Fleer & Hammer, 2014). Four out of the five studies reported the use of a theoretical orientation informing the research, including social capital (Gibson et al, 2015), interpretative phenomenological (Harman et al, 2014), cultural-historical (Fleer & Hammer, 2014) and critical social capital (Mulcahy et al, 2010) theories.…”
Section: Resultsmentioning
confidence: 99%
“…Data in the five papers were collected using individual and/or focus group interviews (Gibson et al, 2015; Harman et al, 2014; Keam et al, 2018; Mulcahy et al, 2010) and video recordings (Fleer & Hammer, 2014). Interviews focused on parents and their experiences and perspectives of their involvement at playgroup, including benefits and constraints of participation for parents, families and communities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations